2019
DOI: 10.1111/tid.13125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of valganciclovir prophylaxis in high‐risk (D+/R−) renal transplant recipients experiencing delayed graft function

Abstract: Background Cytomegalovirus (CMV) outcomes with valganciclovir prophylaxis in renal transplant recipients experiencing delayed graft function (DGF) are unclear. Methods This single center, retrospective, cohort study of CMV high‐risk (D+/R− with alemtuzumab induction) deceased donor renal transplant recipients receiving valganciclovir prophylaxis assessed CMV outcomes in patients experiencing DGF (n = 72) versus those with immediate graft function (IGF; n = 66). Results Cytomegalovirus viremia by 12 months occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…39 Similar to our study, Freedman et al 40 found no statistically significant association between CMV and DGF when looking specifically at the CMV high-risk population. 40 Finally, in contrast to our study, assessing risk for DGF and pneumonia, a few studies reported an increased risk of pneumonia among recipients with DGF. [41][42][43] This study has the expected limitations of a single-center observational study, reflecting our specific population and clinical approach.…”
Section: Discussionsupporting
confidence: 89%
“…39 Similar to our study, Freedman et al 40 found no statistically significant association between CMV and DGF when looking specifically at the CMV high-risk population. 40 Finally, in contrast to our study, assessing risk for DGF and pneumonia, a few studies reported an increased risk of pneumonia among recipients with DGF. [41][42][43] This study has the expected limitations of a single-center observational study, reflecting our specific population and clinical approach.…”
Section: Discussionsupporting
confidence: 89%
“…The data in this article are in line with a study by Khurana et al who found that transplant recipients receiving prophylaxis in dosages adjusted for eGFR are at an increased hazard of subsequent CMV prophylaxis breakthrough infections [12]. Freedman et al found 15/138 (11%) breakthrough CMV infections, of which more than half (11/15) were related to underdosing of valganciclovir [13]. In this study DGF was not identified as a risk factor for CMV breakthrough.…”
Section: Discussionsupporting
confidence: 89%
“…The paramount adverse impact on CMV infection after KT is considered as a potential harm factor for acute allograft rejection [ 74 , 75 ]. CMV can indirectly cause dysregulation in the immune system by increasing the amount of inflammatory cytokine which could augment the immune response, which would accelerate the collagen synthesis in allograft and might participate in the risk of renal acute graft rejection [ 76 , 77 ]. Therefore, anti‐CMV prophylaxis is a new challenge associated with the protection of acute allograft dysfunction after KT.…”
Section: Discussionmentioning
confidence: 99%